CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Variation in Population Structure and Standing Stocks of Kelp Along Multiple Environmental Gradients and Implications for Ecosystem Services - Hege Gundersen; Eli Rinde; Trine Bekkby; Kasper Hancke; Janne K. Gitmark; Hartvig Christie (Frontiers in Marine Science, 2021)
There is an increasing focus on ecosystem services provided by macroalgae worldwide, many which depend on its structural and morphological characteristics. Here we investigated how characteristics of canopy kelp plants of Laminaria hyperborea varies along the Norwegian part of the NE Atlantic. Ten characteristics related to size, allometry, density, biomass and epiphytes were analyzed along wide gradients of depth, wave exposure and latitude. The analyses were performed on a compiled dataset of 630 scuba samples from different research and monitoring projects along the Norwegian coast (58-71°N). The largest kelps, highest biomass, and highest biomass of epiphytic algae was found in Mid-Norway (63-65°N). While most size-related kelp characteristics were reduced with water depth, they were enlarged with wave exposure. The developed statistical models can be used to calculate site-specific values (and their variation) of the different characteristics at any location based on latitude, depth and wave exposure. These can further be used to map kelp derived ecosystem services. We predicted region-specific estimates of total plant weight, kelp density and kelp biomass. Moreover, the models were applied to estimate living biomass (56 million tonnes fresh weight), carbon standing stock (2.6 million tonnes carbon or 9.5 million tonnes CO2), and carbon sequestration potential (0.46 million tonnes per year) for the Norwegian kelp forests, that were estimated to cover about 5 355 km 2 . The site- and region-specific estimates are relevant to kelp forest management and for blue carbon accountings.

The Abundance of Kelp Is Modified by the Combined Impact of Depth, Waves and Currents - Trine Bekkby; Cecilie Smit; Hege Gundersen; Eli Rinde; Henning Steen; Lise Tveiten; Janne K. Gitmark; Stein Fredriksen; Jon Albretsen; Hartvig Christie (Frontiers in Marine Science, 2019)

Shifts Between Sugar Kelp and Turf Algae in Norway: Regime Shifts or Fluctuations Between Different Opportunistic Seaweed Species? - Hartvig Christie; Guri S. Andersen; Trine Bekkby; Camilla W. Fagerli; Janne K. Gitmark; Hege Gundersen; Eli Rinde (Frontiers in Marine Science, 2019)

Status, trends and drivers of kelp forests in Europe: an expert assessment - R. M. Araújo; J. Assis; R. Aguillar; L. Airoldi; I. Bárbara; I. Bartsch; T. Bekkby; H. Christie; D. Davoult; S. Derrien-Courtel; C. Fernandez; S. Fredriksen; et al. (Biodiversity and Conservation, 2016)

Genetic diversity of the NE Atlantic sea urchin Strongylocentrotus droebachiensis unveils chaotic genetic patchiness possibly linked to local selective pressure - K. M. Norderhaug; M. B. Anglès d’Auriac; C. W. Fagerli; H. Gundersen; H. Christie; K. Dahl; A. Hobæk (Marine Biology, 2016)

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Assessment ofsolatium hougasii in Washington and Mexico as a source of resistance to late blight - D. A. Inglis; C. R. Brown; B. G. Gundersen; L. D. Porter; J. S. Miller; D. A. Johnson; H. Lozoya-Saldaña; K. G. Haynes (American Journal of Potato Research, 2007)

Soil Solution Chemistry and Element Fluxes in Three European Heathlands and Their Responses to Warming and Drought - Inger K. Schmidt; Albert Tietema; Dylan Williams; Per Gundersen; Claus Beier; Bridget A. Emmett; Marc Estiarte (Ecosystems, 2004)

Seasonal dynamics of benthic O 2 uptake in a semienclosed bay: Importance of diffusion and faunal activity - Ronnie N. Glud; Jens K. Gundersen; Hans Røy; Bo Barker Jørgensen (Limnology and Oceanography, 2003)
The benthic O 2 uptake and the O 2 microdistribution in a coastal sediment of Aarhus Bay, Denmark, were investigated during a seasonal study. Measurements were performed in situ by a profiling lander and a flux chamber lander, as well as on recovered sediment cores. The O 2 penetration depth, the diffusive O 2 uptake, and the volumespecific O 2 consumption rate strongly depended on the seasonal changes in bottom water O 2 concentration and the sedimentation of organic carbon. The in situ O 2 penetration depth varied between 0.5 mm in summer and 4.5 mm in winter. The diffusive O 2 uptake varied between 8 and 30 mmol m −2 d −1 , whereas the volume‐specific O 2 consumption rate varied by a factor of 13. The O 2 distribution was very sensitive to environmental controls, and microprofiles obtained in the laboratory tended to overestimate the in situ O 2 penetration depths and underestimate the in situ diffusive O 2 uptake. Three‐dimensional O 2 flux calculations based on in situ microtopographic mapping showed that the actual diffusive exchange rate was ~10% higher than the simple one‐dimensional, microprofilederived diffusive O 2 exchange. The total O 2 uptake measured in the laboratory showed less distinct seasonal variation, but on the average, it was ~20% higher than the diffusive O 2 uptake. The difference reflected the microtopography of the sediment surface and the contribution from benthic macrofauna. In situ total O 2 uptake was generally twice as high as laboratory rates, reflecting a higher fauna‐related O 2 consumption in the larger enclosures incubated in situ. Annually, the in situ three‐dimensional diffusive O 2 consumption was 6.2 mol O 2 m −2 , whereas the additional benthos‐mediated O 2 uptake was 3.9 mol O 2 m −2 . Thus, 40% of the total O 2 uptake was due to faunal activity and respiration. The present study demonstrates the importance of realistic faunal representation during sediment incubations in order to obtain correct benthic mineralization rates.

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)